The Edinburgh dictionary of modernism - Kolocotroni, Vassiliki; Taxidou, Olga (Edinburgh University Press, 2018)
"This Dictionary collects, categorises and intersects literary, aesthetic, political and cultural terms that in one way or another came into being through the debates, conflicts, co-operations, experiments- individual and collective - that characterised modernism. In concise entries from international experts, it presents the terms, categories, concepts, tropes, movements, forged through the modernist upheavals (at once aesthetic and political), highlighting their genealogy, their modernist newness, and their historical longevity."